Ferrate (VI) Oxidation Is an Effective and Safe Way to Degrade Residual Colistin - a Last Resort Antibiotic - in Wastewater - Wang, Liqi; Lv, Shiming; Wang, Xiaoying; Liu, Baosheng; Wang, Zhong (Frontiers in Veterinary Science, 2021)
The rise of novel mcr mobile resistance genes seriously threatens the use of colistin as a last resort antibiotic for treatment of multidrug-resistant Gram-negative bacterial infections in humans. Large quantities of colistin are released annually into the environment through animal feces. This leads to environmental toxicity and promotes horizontal transmission of the mcr gene in aqueous environments. We examined colistin degradation catalyzed by the presence of strong oxidant Fe (VI). We found almost complete colistin degradation (> 95 %) by Fe (VI) at initial colistin levels of 30 mM at a molar ratio of Fe (VI): colistin of 30 using an initial pH 7.0 at 25℃ for 60 min. The presence of humic acid did not alter the degradation rate and had no significant impact on the removal of colistin by Fe (VI). Quantitative microbiological assays of Fe (VI)-treated colistin solutions using Escherichia coli, Staphylococcus aureus and Bacillus subtilis indicated that the residual antibacterial activity was effectively eliminated by Fe (VI) oxidation. Luminescent bacteria toxicity tests using Vibrio fischeri indicated that both colistin and its degradation products in water were of low toxicity and the products showed decreased toxicity compared to the parent drug. Therefore, Fe (VI) oxidation is a highly effective and environment-friendly strategy to degrade colistin in water.